Data structures and program design in C - Kruse, Robert L. (Robert Leroy); Tondo, Clovis L.;Leung, Bruce P. (London, United Kingdom : Prentice-Hall International Inc., 1997)
Describing programming methods and tools using the C programming language, this text emphasizes problem specification and program design, analysis, testing and verification and program correctness.
Programming Principals -- Introduction to Software Engineering -- Lists -- Linked Lists -- Searching -- Tables and Information Retrieval -- Sorting -- Recursion -- Binary Trees -- Trees and Graphs -- Case Study: The Polish Notation -- Mathematical Methods -- Removal of Recursion -- An Introduction to C -- Index
Includes bibliographical references and index.
Keywords: C (COMPUTER PROGRAM LANGUAGE)